2021
DOI: 10.3389/fonc.2021.598017
|View full text |Cite
|
Sign up to set email alerts
|

m6A RNA Methylation Regulators Impact Prognosis and Tumor Microenvironment in Renal Papillary Cell Carcinoma

Abstract: Accumulating evidence has proven that N6-methyladenosine (m6A) RNA methylation plays an essential role in tumorigenesis. However, the significance of m6A RNA methylation modulators in the malignant progression of papillary renal cell carcinoma (PRCC) and their impact on prognosis has not been fully analyzed. The present research set out to explore the roles of 17 m6A RNA methylation regulators in tumor microenvironment (TME) of PRCC and identify the prognostic values of m6A RNA methylation regulators in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…For example, Zhang et al found that IGF2BP3 is generally up-regulated in 18 TCGA tumors, and the high expression level of IGF2BP3 affects the immune microenvironment and drug sensitivity, leading to poor prognosis [ 24 ]. Simultaneously, IGF2BP3 was identified as an independent prognostic indicator in renal papillary cell carcinoma [ 25 ], hematological malignancies [ 26 ], and prostate cancer [ 27 ]. Consistent with these studies, we found that IGF2BP3 was upregulated in patients with NPC and NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al found that IGF2BP3 is generally up-regulated in 18 TCGA tumors, and the high expression level of IGF2BP3 affects the immune microenvironment and drug sensitivity, leading to poor prognosis [ 24 ]. Simultaneously, IGF2BP3 was identified as an independent prognostic indicator in renal papillary cell carcinoma [ 25 ], hematological malignancies [ 26 ], and prostate cancer [ 27 ]. Consistent with these studies, we found that IGF2BP3 was upregulated in patients with NPC and NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide a framework for the development and usage of m6A WREs inhibitors in melanoma treatment. However, these studies focused on the m6A WREs at the level of a single gene, whereas the combination of m6A WREs with clinicopathological parameters has shown great potential in the prognosis prediction of cancers, such as hepatocellular carcinoma, lung squamous cell carcinoma, and renal papillary cell carcinoma [ 40 – 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several evidences have displayed the involvement of m6A regulators modification in innate and adaptive immune responses [ 42 , 46 ], but its mechanism of shaping the tumor microenvironment in melanoma remains poorly understood. We have verified the oncogenic functions of IGF2BP3 in melanoma via cell functional experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients receiving immune checkpoint therapies, the clinical benefits were significantly higher in patients with high m 6 A scores ( 119 ). The expressions of 17 m 6 A RNA methylation regulators were closely related to the immunity and malignant progression of papillary renal cell carcinoma ( 120 ).…”
Section: Associations Of M 6 a Rna Methylation With Tumor Immunity In Various Cancersmentioning
confidence: 99%